Successful outcome of pregnancy in a case of systemic lupus erythematosus : a case report - Mohan, Gurinder; Kaur, Avleen; Khullar, Umang (International Journal of Advances in Medicine, 2019)
Systemic lupus erythematosus (SLE) is a multisystem, auto immune connective tissue disease that commonly affects women of reproductive age and may coexist with pregnancy. The autoantibodies and immune complexes lead to damage of various organs and tissues. Pregnant woman with SLE have increased risk of spontaneous abortion, preterm delivery, intrauterine growth retardation, preeclampsia, neonatal lupus, stillbirth and intrauterine fetal death. The therapeutic intervention with anticoagulants, steroids, immunosuppressive agents pose a high risk to both mother and fetus. A multidisciplinary approach and close medical, obstetrical and neonatal monitoring leads to optimal outcome. Authors describe a successful management of an antenatal patient with positive antinuclear antibody, anti-ds DNA antibody and antiphospholipid antibody with bad obstetric history. She underwent an emergency cesarean section and delivered a healthy female child.